Generation of structured hexahedral meshes in volumes with holes - Ruiz-Gironés, E.; Sarrate, J. (Finite elements in analysis and design, 2010)
The submapping method is one of the most used techniques to generate structured hexahedral meshes. This method splits the geometry into pieces logically equivalent to an hexahedron. Then, it meshes each patch keeping the mesh compatibility between pieces by solving an integer linear problem. The quality of the final discretization is governed by the objective function that defines the linear problem. Thus, in this work we propose a new objective function that better distributes the number of intervals among the edges of the geometry. In addition, special procedures have to be developed in order to apply the submapping method to volumes with holes. This article also presents two original contributions to efficiently mesh geometries that contain holes. Finally, it presents several numerical examples that show the applicability of the developed algorithms.